El Oriente: The afternoon newspaper [Sep 1926] - Eliseo Salazar (My University, 1926)
Diario regional independiente; informativo; de publicidad comercial, galardonado con diploma de honor en 1923 y diploma y medalla de oro en 1924 por la municipalidad de Iquitos; septiembre de 1926

Independent daily regional newspaper; informative; commercial publicity, awarded a diploma of honor in 1923 and a diploma and gold medal in 1924 by the municipality of Iquitos; september 1926
El Oriente: El diario de la tarde [Sep 1926]
Keywords: Publicity; Politics and government; Commerce; Health and medicine; Accounting and finance; Arts; Sports and recreation; Nationality heros; Military; Education